Long-term dynamics of avifauna and bird population of Chelyabinsk International Airport Balandino, Russia - Valeria A. Gashek; Valeriy D. Zakharov (Ecosystem Transformation, 2022)
Over 30-year study period (1990–2021), 144 bird species, including 54 nesting species, were registered on the territory of the Chelyabinsk International Airport Balandino. Total bird population density varied from 147 ind./km² in 1990 to 215 ind./km² in 2020. In different years, dominant species in this area were Alauda arvensis, Motacilla flava, Saxicola rubetra, S. torquata, and Passer montana. In the first years of research, a significant decrease in the number of the most widespread species (Corvus frugilegus, C. monedula, Columba livia, Larus barabensis, L. canus, and L. ridibundus), crossing the airfield during seasonal and diurnal (forage) migrations, was revealed. This was caused both by decrease of population of some species (C. frugilegus) in the European and Ural-Siberian parts of their range, and by the deterioration of the state of forage lands on the airport territory after the elimination of solid waste landfills and a decrease of farmland areas nearby.